Inflammasome-targeting natural compounds in inflammatory bowel disease: Mechanisms and therapeutic potential - Xu, Qiuyun; Sun, Weichen; Zhang, Jie; Mei, Youmin; Bao, Jingyin; Hou, Shengping; Zhou, Xiaorong; Mao, Liming (Frontiers in Immunology, 2022)
Inflammatory bowel disease (IBD), mainly including Crohn’s disease and ulcerative colitis, seriously affects human health and causes substantial social and economic burden. The pathogenesis of IBD is still not fully elucidated, whereas recent studies have demonstrated that its development is associated with the dysfunction of intestinal immune system. Accumulating evidence have proven that inflammasomes such as NLRP3 and NLRP6 play a prominent role in the pathogenesis of IBD. Thus, regulating the activation of inflammasomes have been considered to be a promising strategy in IBD treatment. A number of recent studies have provided evidence that blocking inflammasome related cytokine IL-1β can benefit a group of IBD patients with overactivation of NLRP3 inflammasome. However, therapies for targeting inflammasomes with high efficacy and safety are rare. Traditional medical practice provides numerous medical compounds that may have a role in treatment of various human diseases including IBD. Recent studies demonstrated that numerous medicinal herb derived compounds can efficiently prevent colon inflammation in animal models by targeting inflammasomes. Herein, we summarize the main findings of these studies focusing on the effects of traditional medicine derived compounds on colitis treatment and the underlying mechanisms in regulating the inflammasomes. On this basis, we provide a perspective for future studies regarding strategies to improve the efficacy, specificity and safety of available herbal compounds, and to discover new compounds using the emerging new technologies, which will improve our understanding about the roles and mechanisms of herbal compounds in the regulation of inflammasomes and treatment of IBD.